Legal Protection Of Consumers In Credit Car Sales Agreements (Study At Pt BII Finance Center) - Dian Utami (Journal of Law Science, 2020)
In addition to the sale and purchase as regulated in Article 1457 of the Civil Code, in practice other buying and selling agreements can occur as long as they fulfill the legal requirements of the agreement such as a cash sale and purchase agreement, a credit sale and purchase agreement, a sale and purchase agreement with a guarantee or without a guarantee. In a sale and purchase agreement, the buyer will usually always examine the condition and condition of an item to be purchased, whether it is in good condition or whether there is a defect. However, if the goods being traded are in the form of four-wheeled vehicles (cars) on credit, then the buyer may not be able to find out the condition of the four-wheeled vehicles (cars) on credit if they are not tested directly to find out whether they function or not. For this reason, someone who buys a four-wheeled vehicle (car) can sue the seller if the four-wheeled vehicle (car) he has purchased turns out to have hidden defects that were not known at the time of purchase. Consumers' obligations in accordance with Article 5 of the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection, after the existence of the UUPK, the protection of consumers from abuse of the situation is getting better because based on Article 18 of the UUPK it is prohibited to contain certain standard clauses in the agreement between consumers and business actors . Legal Efforts that can be taken by consumers of PT BII Finance Center if they are harmed in the Sale and Purchase of Credit Cars, namely the resolution of problems in the event of non-performing loans in financing companies, is carried out in two ways, namely by litigation and non-litigation. then the protection of consumers from abuse of circumstances is getting better because based on Article 18 of the UUPK it is prohibited to contain certain standard clauses in the agreement between consumers and business actors. Legal Efforts that can be taken by consumers of PT BII Finance Center if they are harmed in the Sale and Purchase of Credit Cars, namely the resolution of problems in the event of non-performing loans in financing companies, is carried out in two ways, namely by litigation and non-litigation. then the protection of consumers from abuse of circumstances is getting better because based on Article 18 of the UUPK it is prohibited to contain certain standard clauses in the agreement between consumers and business actors. Legal Efforts that can be taken by consumers of PT BII Finance Center if they are harmed in the Sale and Purchase of Credit Cars, namely the resolution of problems in the event of non-performing loans in financing companies, is carried out in two ways, namely by litigation and non-litigation.